The Aims and Objectives of Unions and Management in Relation to Each Other - John R. Stockham (Washington University Law Quarterly, 1956)
While I do not by any means decry sincere efforts to establish mutuality of understanding and constructive relationships, I feel that we must be aware of the realities existing in the ordinary union-management relations. Regardless of what the ultimate ideal might be, lawyers must concern themselves with the aims and objectives as they relate to particular situations and to specific management and union personalities. Of course, there should be constant, intense efforts to improve relationships, but such efforts, like pious preachments, will be meaningless unless the real nature of the relationships is thoroughly understood. It is impossible to generalize as to what the objectives of either party might be in any particular situation because many variables affect the relationship. These variables include such factors as the general economic and political climate, the economics of the company, the industry, and the community, the history of the relationship, the personalities involved, technological developments and many others. These variables mean that specific objectives are ever changing and dynamic. While some broad generalities might be set forth, exceptions almost always have to be made.
Keywords: Labor management relations